2014
DOI: 10.3329/bjas.v43i3.21645
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy diagnosis in Black Bengal goat by progesterone assay

Abstract: Pregnancy is the main event in the life of a female mammal to reproduce the progeny and maintain the descents of the species. Progesterone level in the plasma is one of the indications of stages of pregnancy of an individual and the present study was undertaken to determine the progesterone level in different stages of pregnant Black Bengal does and to correlate blood progesterone level with stages of pregnancy in Black Bengal does. For this experiment the blood samples were collected from different stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…deaths during the peri-implantation period (Bazer and Thatcher, 2017) occurred in the nonreturn to estrus (Karadaev, 2015) with high levels of progesterone at 25-30 days post-mating (Islam et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…deaths during the peri-implantation period (Bazer and Thatcher, 2017) occurred in the nonreturn to estrus (Karadaev, 2015) with high levels of progesterone at 25-30 days post-mating (Islam et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…The non-return to oestrus in a cycle is a very early pregnancy diagnosis after the mating (Karadaev, 2015). Islam et al (2014) reported progesterone concentrations of 1.5 ng/mL, 6.6-9.3 ng/mL, and 14-15.5 ng/mL respectively on 25-30, 60-70, and 90-92 days of pregnancy. However, a high concentration of progesterone has not proven pregnancy because it could not differentiate between mid-cycle, true or false pregnancy (Devalal et al, 2018).…”
Section: Discussionmentioning
confidence: 99%